Teachers’ Perspectives on the Need for Integrating Guidance and Counseling Services in Schools - Damanik, Cristin Mutiara; Budi Astuti (Universitas PGRI Yogyakarta, 2026)
The integration of Guidance and Counseling (BK) services at SMP Negeri 1 Bagan Sinembah, Riau, has not been implemented in accordance with the provisions of Law Number 20 of 2003 on the National Education System. This study aims to evaluate teachers' perceptions of the need for integrating BK services. The research method employed is a quantitative approach, utilizing a survey that involved 35 teachers as respondents. The results show that the majority of respondents (31.43%) fall into the